Carbene-catalyzed asymmetric construction of atropisomers - Song, Runjiang (2022)
Atropisomeric molecules have found proven applications and have shown promising potential in chemistry and medicine. The design of N-heterocyclic carbene (NHC) catalyzed reactions to construct atropisomerically enriched molecules has emerged as an important research topic in recent years. These reactions include kinetic resolutions, asymmetric desymmetrizations, central-to-axial chirality conversions, and cycloadditions. This Minireview evaluates and summarizes the progress in NHC-based organic catalysis for access to atropisomers, and briefly states our personal perspectives on the future advancement of this topic. NHC catalysis has provided rich and unique reaction modes that have led to success in the asymmetric synthesis of central-chiral molecules. It is expected that similar success could also be achieved in developing NHC catalysis to prepare atropisomeric molecules, including those not easily accessible by other methods.